Experiences of Violence Against Lesbian and Bisexual Women in Brazil. Issue 2 (14th January 2022) - Rufino, Andréa Cronemberger; Filho, Carlos Eugênio Wall Barbosa de Carvalho; Madeiro, Alberto
Abstract: Background: Lesbophobia and biphobia are manifestations of homophobic violence directed at lesbian and bisexual women that results in daily violation of rights and social exclusion. Aim: To describe experiences of the violence against lesbian and bisexual women in Brazil. Methods: Sequential mixed methods study was carried out in 2 stages. In the first one, quantitative, an electronic questionnaire was applied to women from all regions, with questions about sociodemographic characteristics, self-identification and lesbophobic and biphobic events. In the second one, qualitative, lesbian, and bisexual women were interviewed face to face about the violence suffered. Outcomes: The chi-square test was applied to compare violence against lesbian and bisexual women (type of violence, place of aggression, gender and age range of the aggressor, bond with the aggressor, repetition of violence, and denunciation of violence) and the content analysis for qualitative data (main categories of analysis were events of violence, denunciation, and consequences of violence). Results: The report of violence was present in 65% of the answers. There was a predominance of psychological violence (39.8%), in the public environment (63%), practiced by men (73.2%), by strangers (66.2%) and repeatedly (82%). Lesbian women, compared to bisexuals, were more prone to violence in the public environment (59.5% vs 39.5%) and with repetition (84.3% vs 60.6%). The narratives explained intimidating experiences in the family environment (insults, threat of suicide or homicide and false imprisonment) and public (harassment, beatings, and rape). Discriminatory attitudes, insults, and refusal of service in restaurants and bars were recurrent. Clinical Implications: The data provide information that can serve to improve policy initiatives to reduce these episodes. Strengths and Limitations: This is the first study of mixed methods, with national coverage, on lesbophobia and biphobia events in Brazil. Future studies should include women underrepresented in this research as trans women, non-white, less educated, and from the most distant regions of the country. Conclusion: Lesbophobic or biphobic event has harmful repercussions for multiple aspects of these women's lives, including mental health.